Risk of Developmental Disorders in Children of Immigrant Mothers: A Population-Based Data Linkage Evaluation - Abdullahi, I.; Wong, K.; Mutch, R.; Glasson, E.; de Klerk, N.; Cherian, S.; Downs, Jennepher; Leonard, H. (Mosby, Inc., 2019)
Objectives: To evaluate the prevalence and risks of developmental disability (autism spectrum disorder, intellectual disability, and cerebral palsy) in Western Australian children of different groups of foreign-born women. Study design: Western Australian population-based linked data of 764 749 singleton live births from 1980 to 2010 were used to compare disability outcomes among children of foreign-born, Australian-born non-Indigenous, and Indigenous women. The risk of disability was assessed using multinomial logistic regression. Results: Overall, the prevalence of any disability was lowest for the children of foreign-born mothers. From 1980 to 1996 but not from 1997 to 2010, children born to mothers from foreign-born low-income countries had an increased relative risk of autism spectrum disorder with intellectual disability, and children born to foreign-born mothers from upper-middle-income countries had an increased risk of cerebral palsy with intellectual disability. After adjusting for smoking, the relative risks of intellectual disability and cerebral palsy with intellectual disability were markedly decreased in children of Australian-born Indigenous mothers. Conclusions: Although we did not find among children born to foreign-born women an increased prevalence across all the measured developmental outcomes, we did observe an increased risk of autism spectrum disorder with intellectual disability and cerebral palsy with intellectual disability for mothers of some foreign-born groups. Our findings related to smoking in the Indigenous population underscore its possible role on the causal pathway to intellectual disability. Maternal migration is considered a factor on the causal pathway to intellectual disability. Maternal migration may be either a risk or a protective factor on the causal pathway to developmental disabilities and the direct role of migration is inconclusive in our study.